2022
DOI: 10.1007/s00415-021-10955-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the functional impact of cognitive impairment in Huntington’s disease

Abstract: Background Patients with Huntington’s disease (HD) exhibit a variable predominance of cognitive, behavioral and motor symptoms. A specific instrument focusing on the impact of cognitive impairment in HD over functional capacity is lacking. Objective To address the need for a brief and specifically developed HD questionnaire able to capture functional aspects suspected to be sensitive to cognitive impairment. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In summary, current diagnostic criteria for the cognitive syndromes in HD are limited and the need for reliable instruments to assess cognitive status is evident. The PD-CRS shows excellent discriminative properties that have been replicated in two studies and in two different cohorts [ 4 , 23 ]. Despite the lack of specific definitions of MCI and dementia in HD, this tool shows adequate discrimination between cognitive groups.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In summary, current diagnostic criteria for the cognitive syndromes in HD are limited and the need for reliable instruments to assess cognitive status is evident. The PD-CRS shows excellent discriminative properties that have been replicated in two studies and in two different cohorts [ 4 , 23 ]. Despite the lack of specific definitions of MCI and dementia in HD, this tool shows adequate discrimination between cognitive groups.…”
Section: Discussionmentioning
confidence: 94%
“…To meet the minimum standards to deal with the lack of a validated gold standard for global cognitive status in HD, and in absence of specific and well-defined criteria, we developed a two-step approach similar to those previously used [ 4 , 23 ]. The first step was the administration of the Clinical Dementia Rating Scale (CDR) [ 30 ] and the Functional Independence Score (FIS).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, earlier research showed that cognitive impairments and different motor phenotypes may also have an influence on functional capacities in manifest HD [26][27][28]. In particular, dystonia and hypokinetic rigidity have a stronger influence on functional impairments than chorea [2,27].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment is one of the triad of symptoms in manifest HD, representing impairments in attention, verbal fluency, psychomotor speed, executive functioning, memory, and visuospatial functioning (Duff et al., 2010 ; Ross et al., 2014 ), which may appear even in gene‐positive individuals before the onset of motor symptoms (Papoutsi et al., 2014 ; Peavy et al., 2010 ). The cognitive impairment is progressive and a contributing factor for daily disability, which is generally considered to be more debilitating to the patients and their families (Beerens et al., 2013 ; Horta‐Barba et al., 2022 ; Papoutsi et al., 2014 ). During the early stage, clinicians may overlook subtle cognitive impairment in HD patients (Julayanont et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%